A numerical study of strike‐slip bend formation with application to the Salton Sea pull‐apart basin. Issue 5 (11th March 2015) - Ye, Jiyang; Liu, Mian; Wang, Hui
Abstract: How stepovers of strike‐slip faults connect to form bends is a question important for understanding the formation of push‐up ranges (restraining bends) and pull‐apart basins (releasing bends). We investigated the basic mechanics of this process in a simple three‐dimensional viscoelastoplastic finite element model. Our model predicts localized plastic strain within stepovers that may eventually lead to the formation of strike‐slip bends. Major parameters controlling strain localization include the relative fault strength, geometry of the fault system, and the plasticity model assumed. Using the Drucker‐Prager plasticity model, in which the plastic yield strength of the crust depends on both shear and normal stresses, our results show that a releasing bend is easier to develop than a restraining bend under similar conditions. These results may help explain the formation of the Salton Sea pull‐apart basin in Southern California 0.5–0.1 Ma ago, when the stepover between the Imperial Fault and the San Andreas Fault was connected by the Brawley seismic zone. Key Points: At same conditions, a releasing bend is easier to form than a restraining bend The results may help explain the formation of the Salton Sea pull‐apart basin The results may help explain why releasing bends are more common